A Simulation Study on Material Requirement Planning (MRP) System Performance and Lead Time Variability - Gu, Xingfan (2011)
Material requirement planning system has a prominent role in the manufacturing system. Although MRP has being out of favor in recent years compare with some of the modern production planning concepts such as JIT or OPT, it still has its advantages in flexibilities and product customizations. MRP system is one of the few things must learn to all operation management students over the world. The objective of the project is to investigate the relationship between MRP performance and lead time variability. In this research, we successfully conducted a serious of simulation experiments regarding this topic.